1993
DOI: 10.1007/bf02776981
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience with 5 n3(+) early gastric carcinoma cases

Abstract: Of 370 patients who underwent a resection for early gastric carcinoma, 317 (85.6%) were N(-), 28 n1(+), 20 n2(+) and five (1.4%) n3 respectively. In this study, n3(+) early gastric cancers were clinicopathologically evaluated and sites of the metastatic nodes were also defined. In addition, a comparative study in DNA ploidy patterns between primary and metastatic node cell was performed according to Hedley's method using a FACS-IV scan of paraffin-embedded tissues. All n3(+) early gastric cancers showed an ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Indication for endoscopic therapies such as EMR and EMCT is determined by tumor histology, depth and size (mucosal cancer less than 2 cm without ulceration). Since it has been reported that lymph node metastasis is extremely rare in such small mucosal cancers [2,5,10-12], clinicians will not entertain the possibility of lymphadenopathy. If the EGC does not meet the above criteria for endoscopic treatment, gastrectomy with D2 lymph node dissection is performed, and indication for modified gastretomy is determined by intraoperative findings [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indication for endoscopic therapies such as EMR and EMCT is determined by tumor histology, depth and size (mucosal cancer less than 2 cm without ulceration). Since it has been reported that lymph node metastasis is extremely rare in such small mucosal cancers [2,5,10-12], clinicians will not entertain the possibility of lymphadenopathy. If the EGC does not meet the above criteria for endoscopic treatment, gastrectomy with D2 lymph node dissection is performed, and indication for modified gastretomy is determined by intraoperative findings [5].…”
Section: Discussionmentioning
confidence: 99%
“…If the EGC does not meet the above criteria for endoscopic treatment, gastrectomy with D2 lymph node dissection is performed, and indication for modified gastretomy is determined by intraoperative findings [5]. Added to the fact that N3 metastasis of EGC is extremely rare [10-12], detailed preoperative evaluation of lymph nodes is not essential.…”
Section: Discussionmentioning
confidence: 99%